PhD Forum: Evaluating and Designing Routing Protocols for Reliable Distributed Quantum Systems - Nadeem, Huzaifah (Proceedings - Symposium on Reliable Distributed Systems, 2024)
As quantum computers and quantum networks become more capable, it allows for the possibility to use multiple quantum computers as part of a distributed system. Such a distributed system will have applications such as running quantum algorithms in a distributed fashion [7], leadership elections without communication [7], clock synchronisation [10], and a cryptographic protocol called quantum key distribution [1], etc. However, to create a reliable system, it is important that the underlying quantum network can reliably support the necessary communication protocols between quantum nodes. To support reliable communication in a quantum network, quantum routing algorithms - which are algorithms that plan out how to send qubits and over which subset of nodes in the network - is an active area of research. However, various design choices and algorithms exist that are developed without a realistic simulated environment that can provide rich data that can further help develop, improve, and test these algorithms. Such an environment is important because general-purpose algorithms need to take into account detailed information about how the qubit changes over the communication process - as that requirement can vary for different applications - rather than simpler probability based loss models existing algorithms were developed with. Using existing lower-level tools, we are creating a tool will help evaluate and design routing protocol by providing a variety of models - from simple to complex - to support various stages of development, as well as the ability to generate useful data to evaluate how the protocols perform in a realistic quantum network.